LANGUAGE STYLE USED BY ROCKY GERUNG IN INSTAGRAM STATUS - Wiki Tedi Rahmawati; Yunita Mutiara Harahap; Mahroza Mahroza (EXCELLENCE: Journal of English and English Education, 2021)
This study dealt with language style used by Rocky Gerung in Instagram status. It was aimed to describe the types of language style and to find out the most dominant language style used by Rocky Gerung in Instagram status. This study was conducted by using qualitative research design. The source of data was @rockygerungofficial in Instagram. The data were analyzed by using descriptive analysis technique by Miles, Huberman, and Saldana. The result showed that there were 3 concepts of language style used by Rocky Gerung in Instagram, namely intimate style, consultative style, and casual style. In addition, there were 9 sentences (42.86%) for intimate style, 9 sentences (42.86%) for consultative style, and 3 sentences (14.28%) for casual style. The consultative style and intimate style were dominantly used by Rocky Gerung in his Instagram status.